Facial Emotion Recognition Using Deep Neural Network (International Journal of Innovative Research in Engineering & Management, 2023)
The major part in the process of  humanization of systems is the capability of distinguishing  the emotions of the person. In this research paper we  represent the composition of an instinctive system that is  capable of detecting the emotion by using their facial  expressions. Three techniques of neural network are tailored,  educated and subordinated to different jobs, after this the  performance of the network was improved. A live videotape  operation that can currently simulate the person’s emotion  depicts how well the model connects to the world. Since the  invention of computers many technologists and masterminds  are introducing instinctively intelligent systems that are very  helpful to humans mentally and physically. In the previous  decades the usage of computer has increased rapidly which  helps in developing fast literacy systems, where internet has  provided vast quantum of data for teaching the machine.  These two enlargements elevated the exploration on  intelligent learning systems by using neural networks in  favorable ways. The facial emotion detection machine needs  to be trained to get the system ready. The installation of  OpenCV(Open Source Computer Vision) is essential for this  machine. OpenCV is a library that is required for computer  vision.
Keywords: Humanization of Robotics; Instinctively Intelligent System; Live Video tape operation; Smart tone Learning systems; Open CV(Open Source Computer Vision)